Carbonic Anhydrase II Deficiency: A Rare Case of Severe Obstructive Sleep Apnea - di Palmo, Emanuela; Gallucci, Marcella; Tronconi, Elena; Bergamaschi, Rosalba; Cazzato, Salvatore; La Scola, Claudio; Ricci, Giampaolo; Pession, Andrea (Frontiers in Pediatrics, 2018)
The term osteopetrosis describes a group of rare hereditary diseases of the skeleton, characterized by an increase in bone density, caused by a defect in the development or function of osteoclasts. This condition leads to specific craniofacial dysmorphisms associated with upper airway obstruction that may result in obstructive sleep apnea.